PERANCANGAN APLIKASI LAPORAN KINERJA BERBASIS WEB PADA PEGAWAI NON-PNS DI PELAYANAN TERPADU SATU PINTU (PTSP) KECAMATAN PASAR REBO - Ferell Geo Atlanta (2020)
Report performance is a feature that is often used on the internet, on a website, or in other applications. This feature is commonly used to assist users in obtaining employee information, can also be used for employee performance reporting systems. In the employee system at PTSP (Pelayanan Terpadu Satu Pintu ) in Pasar Rebo District, East Jakarta, non-civil servants employees are required to report their performance in the form of reports at the end of the month. When employees make a report, they usually disturb the servants in the PTSP unit. Therefore we need a system that can help employees in making reports in their spare time and not disturbing public services. Making this system can be done by collecting data, analyzing the system, designing the system, and implementing the system. This e-performance system is created using the PHP framework, CSS framework, and MySQL for database management.